CREATIVE CITIZENSHIP: ARTISTIC EDUCATION AS KEY TO CITIZENSHIP EDUCATION IN SCHOOL - Tania Katherine González Ninco; Diana Lorena Salazar Caupaz; Cristian Andrés Cuero (LÍNEA IMAGINARIA, 2025)
This article examines the intersection between civic education and arts education within the school context, emphasizing the formative power of the arts in developing essential cognitive, emotional, and communicative skills for democratic participation, peaceful coexistence, and respect for diversity. Based on a theoretical review, it argues that artistic practices such as theater, music, dance, and painting not only foster creativity but also promote the experiential embodiment of values like empathy, solidarity, justice, and critical thinking. The article calls for a shift away from a merely ornamental view of arts education toward its recognition as a central component of citizenship education, advocating for integrative, participatory, and culturally grounded pedagogical strategies that enable meaningful learning. Furthermore, it demonstrates that aesthetic and playful methodologies create inclusive and emotionally relevant learning environments, particularly for vulnerable student populations. Consequently, the article proposes a transdisciplinary curricular approach that repositions the arts as an ethical and political foundation for shaping reflective, empathetic, and socially engaged citizens from early stages of education. This perspective aligns with international frameworks that identify arts education as a key tool for building democratic, equitable, and resilient societies, positioning schools as vital spaces for enacting and learning active citizenship.